Factors Affecting the Implementation of Accrual-Based Accounting Information Systems and The Impact on Accounting Information Quality-Evidence from Indonesia - Mega Metalia; Sari Indah Oktanti Sembiring; Gandy Wahyu Maulana Zulma (Universitas Batanghari Jambi, 2023)
This study aims to examine the effect of implementing regional financial regulations, employee competence and organizational commitment on the successful implementation of accrual-based accounting information systems and their impact on the quality of accounting information. This research is included in survey research with the type of investigation, this type of research is verification and explanatory research. This research is verificative (verificative research) and is explanatory (explanatory research) or causality (causal study) because this study aims to find out what and to what extent the factors that are estimated to affect a variable with the object of research h implementation of regional financial regulations (X1) , employee competence (X2), organizational commitment (X3), successful implementation of accrual-based accounting information system (Y) and quality of accounting information (Z). The population in this study were all Provincial/District/City Governments in Indonesia. The analytical design used in this research is quantitative data analysis with descriptive method. The quantitative analysis that will be carried out aims to determine the relationship between variables through hypothesis testing using structural equation modeling (Structural Equation Model-SEM) with the Partial Least Square (PLS) approach. The results of the study show that: (1) The implementation of regional financial regulations affects the success of the implementation of an accrual-based accounting information system, (2) Employee competence affects the success of the implementation of an accrual-based accounting information system, (3) Organizational commitment affects the success of the implementation of an accrual-based accounting information system. accruals, (4) The success of the application of accrual-based accounting information system affects the quality of accounting information.